From ecological to anthropogenic factors: unraveling the drivers of blue crab Callinectes sapidus occurrence along the Mediterranean coasts - Anna Gavioli; Giuseppe Castaldelli; David B. Eggleston; Robert R. Christian (Frontiers in Marine Science)
IntroductionNon-native species are widely recognized as threats to biodiversity, ecosystems, and the services they provide to humans. The Mediterranean Sea has a high biodiversity of endemic species and is a hot spot of biological invasions. One of the most recent threats to Mediterranean ecosystems is the invasion of the Atlantic blue crab Callinectes sapidus.MethodsThe occurrences of the crab throughout the Mediterranean coastline were indexed from citizen science through the Global Biodiversity Information Facility. Using spatial analysis and linear mixed models, we investigated geomorphology (i.e., water depth and coastal wetlands extension), water physical variables (i.e., salinity and winter and summer water temperature), water quality variables (i.e., chlorophyll-a, nitrate and orthophosphate) and anthropogenic factors (i.e., ship density and population size) potentially affecting the blue crab occurrence along the coast.ResultsOur results showed that nitrate, as an indicator of riverine nutrient loading, and water depth, as an indicator of slope of the bottom, were the most influential variables in explaining the occurrences of blue crabs. Water temperature and salinity had lesser impacts; anthropogenic factors, such as the density of commercial marine traffic and human population size had no effect on blue crab occurrence.DiscussionThese results sug gest that benthic primary production and shallow water drive blue crab occurrences along the Mediterranean coasts. Even considering data limitations and gaps, our large-scale findings contribute to a broader understanding of the factors that drive blue crab invasion success which, in turn, can inform management actions and outline research needs.